Śladami kopisty Awedyka - Krzysztof Stopka (Ksiegarnia Akademicka Publishing, 2010)
Following Avidicus the copyist. A portrait of the Derszymonowic family, or the micro‑history of cultural transformations among Polish‑Armenians in the 17 th century